2021
DOI: 10.3389/fonc.2021.670917
|View full text |Cite
|
Sign up to set email alerts
|

Role of Long Non-Coding RNAs in Conferring Resistance in Tumors of the Nervous System

Abstract: Tumors of the nervous system can be originated from several locations. They mostly have high mortality and morbidity rate. The emergence of resistance to chemotherapeutic agents is a hurdle in the treatment of patients. Long non-coding RNAs (lncRNAs) have been shown to influence the response of glioblastoma/glioma and neuroblastoma to chemotherapeutic agents. MALAT1, NEAT1, and H19 are among lncRNAs that affect the response of glioma/glioblastoma to chemotherapy. As well as that, NORAD, SNHG7, and SNHG16 have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Furthermore, prior reviews have also primarily concentrated on common lncRNAs noted to have chemoresistance roles without extensive exploration of chemosensitivity of specific lncRNAs. 14 In contrast, this review aims to frame the TMZ response in GBM via exploration of the lncRNAs mediating the three major mechanisms of TMZ resistance: (1) regulation of the DDR, (2) maintenance of glioma stem cell (GSC) identity, and (3) exploitation of hypoxia-associated responses ( Table 1 ).…”
mentioning
confidence: 99%
“…Furthermore, prior reviews have also primarily concentrated on common lncRNAs noted to have chemoresistance roles without extensive exploration of chemosensitivity of specific lncRNAs. 14 In contrast, this review aims to frame the TMZ response in GBM via exploration of the lncRNAs mediating the three major mechanisms of TMZ resistance: (1) regulation of the DDR, (2) maintenance of glioma stem cell (GSC) identity, and (3) exploitation of hypoxia-associated responses ( Table 1 ).…”
mentioning
confidence: 99%
“…NORAD, mainly induced by DNA damage, was initially identified as a lncRNA that played crucial roles in DNA protection and chromosomal stability [35]. Recent studies have demonstrated that NORAD acts as an oncogene in multiple cancers including malignant melanoma, pancreatic cancer, NSCLC and glioblastoma [36][37][38][39]. Importantly, NORAD has been reported to be correlated with chemotherapy resistance in cancer cells, such as resistance to doxorubicin, CDDP and oxaliplatin in neuroblastoma, NSCLC and gastric cancer, respectively [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of non-coding RNAs might also affect response to therapeutic regimens [ 76 ]. For instance, H19 increases ATG7 expression and influences resistance to dopamine agonists [ 15 ].…”
Section: Discussionmentioning
confidence: 99%